VISUAL GAME NOVEL ON READING CLASS: ENHANCEMENT OR USELESS WHEN IT USES IN THE EFL OF ESP CLASSROOMS - Eny Kusumawati (Cordova Journal : languages and culture studies, 2019)
Visual Games Novel (VGN) is effectively seen as a digital evolution books, with music, pictures, and occasionally even voice acting or movies. VGN mostly do not have a game play nor interaction outside of continuing the dialogue with a button press or make a decision even though the typical game drive the user do a lot. This activity applied in EFL reading class to enhance the students’ reading comprehension. Explicit instruction strategy is used to conduct this study, the aim of this qualitative study is to find out the students expressed and their perception toward VGN after being treated with an explicit strategy using VGN in one semester with 8 meetings. An -10 item with open-ended questionnaire which was followed by an in-depth interview. The data were obtained from examining the students’ perceptions towards the use of VGN in reading class. A total of 54 sophomore majoring in Mechatronics and Industrial Electronics Departmentsof an Indonesia state polytechnic (PoliteknikElektronikaNegeri Surabaya). The result showed that mostly students have positive attitudes respond towards VGN and they developed their integrative and instrumental motivation during the treatment.The pedagogy is that combining betweennatural and explicit vocabulary instruction is more effective in promoting reading comprehension to support the VGN. The language practitioners can rely on teaching reading, especially in ESP context, to help improve students’ comprehension in reading.